2009
DOI: 10.4314/thrb.v10i4.45074
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for anaemia in schoolchildren in Tanga region, Tanzania

Abstract: Anaemia is one of the major public health problems affecting more than half of school children along the coast in Tanzania. Due to the multiplicity of its causes it sometimes becomes difficult to find appropriate intervention measures. In order to assist schools in implementing appropriate public health measures for anaemia in Tanga Region of Tanzania risk factors were investigated in school children. A total of 845 schoolchildren age 7-14 years were randomly selected in a cross-sectional survey conducted in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
40
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 29 publications
10
40
5
Order By: Relevance
“…However, prevalence of anemia in our study is much lower than similar reports conducted in Tanzania (79.6%) [19], in Kenya (35.3%) [20], in Abia State, Nigeria (82.6%) [21]. The lower prevalence of anemia in our study might be due to the fact that malaria which is one of the major causes of anemia was less prevalent (3.66%) in this study compared to the previous studies.…”
Section: Discussioncontrasting
confidence: 83%
“…However, prevalence of anemia in our study is much lower than similar reports conducted in Tanzania (79.6%) [19], in Kenya (35.3%) [20], in Abia State, Nigeria (82.6%) [21]. The lower prevalence of anemia in our study might be due to the fact that malaria which is one of the major causes of anemia was less prevalent (3.66%) in this study compared to the previous studies.…”
Section: Discussioncontrasting
confidence: 83%
“…The prevalence of anaemia observed in our study was lower that in a neighbouring district of Magu district (62.6%) (Lwambo et al, 2000) and other places in Tanzania (Tatala et al, 2008). One explanation for this difference could be variations in nutrition status or risks factors for anaemia.…”
Section: Discussioncontrasting
confidence: 83%
“…One explanation for this difference could be variations in nutrition status or risks factors for anaemia. Hookworm, schistosomiasis and malaria are major causes of anaemia (Sturrock et al, 1966;Olsen et al, 1998;Tatala et al, 2008;Koukounari et al, 2008) with hookworm accounting for up to 35%-73% of the iron-deficiency anaemia in Africa (Stoltzfus et al, 1997). In this study, the mean Hb levels were observed to decrease with increase in hookworm egg intensity.…”
Section: Discussionmentioning
confidence: 99%
“…The interactions between hookworm infections and anemia were demonstrated in primary schoolchildren living in India 20 , Zimbabwe 17 and Tanzania 26 . Nevertheless, some surveys that attempted to characterize the relationship between hookworm disease and hemoglobin levels failed to find a conclusive association between these variables.…”
Section: Discussionmentioning
confidence: 99%